Do alcohol-dependent patients show different neural activation during response inhibition than healthy controls in an alcohol-related fMRI go/no-go-task? - Czapla, Marta; Bäuchl, Christian; Simon, Joe J.; Friederich, Hans-Christoph; Mann, Karl; Herpertz, Sabine (Psychopharmacology, 2017)
Rationale Alcohol dependence is associated with impaired response inhibition and heightened cue reactivity towards alcohol-related stimuli. Several brain areas, but mainly prefrontal structures, have been linked to response inhibition in addiction. This study aimed at combining both aspects: salience of drug-associated cues and response inhibition using a go/no-go task with alcohol-associated stimuli during functional magnetic resonance imaging (fMRI).
Gesehen am 09.05.2018